Effect of Twine Thickness on The Size Selectivity of The Dominant Catch of Bottom Gill Nets in Inner Ambon Bay - R Rananmasse, Beatrix; Tupamahu, Agustinus; Haruna, Haruna (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
There are several factors that affect the selectivity of gillnet, including mesh size and twine thickness of netting. The objective of this study is to estimate the level of selectivity of different mesh size and twine thickness on the dominant catch of bottom gillnets. The fishing experiment conducted in Inner Ambon Bay for 9 fishing trips. Data analysis used Kitahara method’s to estimate the selectivity of the mesh size of 3.81, 4,45 and 5.08 cm with twine thickness of netting 0.25 and 0.30 mm to the total length of the dominant catch. The results showed that there are two species of fish dominated catch i.e Upeneus taniopterus dan Selar crumenophthalmus. The frequency distribution of total length of the dominant catch from three mesh sizes tested for both 0.25 and 0.30 mm twine diameter tends to be bimodal, where the 0.25 mm is caught higher than 0.30 mm twine diameter. The probability of the catch of small and large fish for each mesh size was higher at 0.25 mm than 0.30 mm twine diameter.